Inertial Navigation System Design Using Inertial Measurement Unit 10 DoF on Diver Propulsion Vehicle - Ardiansyah, Alief; Arifin, Imam; Pratama, Mahardhika; R, Agung Imam (IPTEK Journal of Proceedings Series, 2019)
Navigation system on DPV uses an analog compass to display the direction of the displacement angle of the vehicle through the degree of angle and the cardinal direction. It canâ€™t display other data, such as the orientation angle and dive depth, which are needed to optimize the performance of DPV. INS is used as navigation system, where within the system there are IMU and computer device. INS works with measuring linear acceleration, rotation rate and magnetic field using accelerometer, gyroscope, and magnetometer on IMU. The reading result are processed by computer device using digital low-pass filter, Madgwick quaternion, and Euler angles to obtain angle orientation data in the form of roll, pitch, and yaw angles. The IMU on INS is configured with a pressure sensor that works with measuring hidrostatic pressure to obtain dive depth. Obtained results of orientation angle measurements that has the furthest error value ofÂ  3.00o, with the furthest average error valueof 0.96o, and the furthest noise value of at steady state of 1.00o. Results of depth measurement has furthest error value of 2.00 cm, with furthest average error value of 1.30 cm, and furthest noise value at steady state of 0 cm.